The Influence of Customer Value Theory Attitude and Online Buy-ing Behavior During the Covid-19 Pandemic in Indonesia - Rafi Mohammad Ihsan; Kurniawati Kurniawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the influence of Customer Value Theory on Attitude and Online Buying Behavior as dependent variables during the Covid-19 pandemic in Indonesia. The collection method in this study was by non-probability sampling method and a purposive sampling technique. The data used in this study is quantitative data obtained from a questionnaire with a total of 189 respondents. With a 5-point Likert Scale it ranges from 1 (Strongly Disagree) to 5 (Strongly Agree). The results of the study revealed that there is a positive relationship between Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, Convenience, Wider Selection, Price, Health Aspect to Attitude, and Shopping Intentions to Online Buying Behavior. Managerial implications in this study can provide advice to online shops about changing consumers' purchasing behavior, in this case, online shops must create a good and good website so that the web is informative and easy to understand by consumers. In addition, online shops must also maintain product quality so that they are always available, online shops must also give a good impression, one of which is by offering discounts and gifts so that consumers are interested in shopping online.